2019
DOI: 10.1167/iovs.18-26393
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Morphologic Characteristics of Optic Disc on Choroidal Thickness in Young Myopic Patients

Abstract: Citation: Chen Q, He J, Yin Y, et al. Impact of the morphologic characteristics of optic disc on choroidal thickness in young myopic patients. Invest Ophthalmol Vis Sci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 40 publications
(39 reference statements)
8
44
0
Order By: Relevance
“…8,23 A recent study by our team suggested that PPA area in young patients with high myopia correlated significantly and negatively with pChT and mChT, even in early myopic stages. 15 The present study found that BMOD and BTA were more sensitive independent factors associated with mChT compared with PPA area (Table 3), and BTA could be a more sensitive independent factor associated with pChT ( Table 4).…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…8,23 A recent study by our team suggested that PPA area in young patients with high myopia correlated significantly and negatively with pChT and mChT, even in early myopic stages. 15 The present study found that BMOD and BTA were more sensitive independent factors associated with mChT compared with PPA area (Table 3), and BTA could be a more sensitive independent factor associated with pChT ( Table 4).…”
Section: Discussionsupporting
confidence: 49%
“…The protocol for this cross-sectional study was consistent with those of previous studies. 15,27 The systolic blood pressure (SBP) and diastolic blood pressure (DBP) of the students were measured. The mean arterial pressure (MAP) was calculated using the following formula: (SBP + 2 × DBP)/3.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All subjects have understood the study protocol and signed informed consent forms. The protocol was consistent with those of previous studies ( 20 , 21 ).…”
Section: Methodssupporting
confidence: 70%